Critique’s Role in the Development of Design Literacy in Beginning Design Education - Yorgancıoğlu, Derya; Tunali, Sevinç (RChD: creación y pensamiento, 2020)
This study examines the development of design literacy for first year architecture students in their beginning design education phase. It focuses on the contribution of design critique in the formation of repertoires for design thinking and doing for first year students. The inquiry is based on the findings of a qualitative case study involving 26 first year design students and six design studio tutors in a Bachelor of Architecture degree programme. Data was collected through focus groups, in-depth interviews, and studio observations, and was analysed using content analysis technique. Research findings indicate that design critiques initiate a transformation process in first year design students in which they begin to grasp how designers think and act. The collaborative effort of the tutor and students, sharing their ideas and re-constructing design knowledge, is realized through the development of new communication methods in design critique sessions. We suggest that when the development of interactive and critical communication skills is embedded in the formation of a community of learners during their first year in a design studio setting, 'learning to criticize' becomes a component of design literacy.